CORPORATE GOVERNANCE – WAY OF GOVERNANCE FOR MODERN COMPANIES - Alina HAGIU; Marinela BARBULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2016)
Through corporate governance is aimed the building of a structure enabling a wide degree of freedom, within the law, and includes several changes of principle in accordance with international standards of transparency. A good governance within an organization mitigate risk, increase performance, pave the way towards financial markets, brings competitive goods and services on market, improves management style, show transparency towards all stakeholders and social responsibility. The lack of some mandatory rules and structures can lead to chaos in business. The paper aims to present the role and the importance of the corporate governance for modern companies, as well as the principles on which this is based. In order to do that we also identified the main ways to quantificate the level of corporate governance, including also the non-financial performance criteria used by investors to assess companies listed on stock exchange.